2014
DOI: 10.1007/s12031-014-0390-8
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of TRPC5 in Cortical Lesions of the Focal Cortical Dysplasia

Abstract: Focal cortical dysplasias (FCDs) are frequently associated with the medical refractory epilepsy in both children and adults. Transient receptor potential canonical channel 5 (TRPC5), a receptor-operated cation channel, has been well recognized as a regulator in the central nervous system. Here, we examined the expression and cellular distribution of TRPC5 in the specimens from patients with FCDIa (n = 14), FCDIIa (n = 12), and FCDIIb (n = 12) compared with the age-matched control cortex (CTX). TRPC5 mRNA and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…In other words, the localization pattern of the [ 125 I]TZ66127 ARG signal matched well with the pattern of TRPC5 IHC staining signal in the rat brain sections. These results are in agreement with previous findings for TRPC5 region‐specific protein expression . Together, our results clearly demonstrate a widespread distribution of TRPC5‐specific binding sites in the rat brain.…”
Section: Resultssupporting
confidence: 93%
“…In other words, the localization pattern of the [ 125 I]TZ66127 ARG signal matched well with the pattern of TRPC5 IHC staining signal in the rat brain sections. These results are in agreement with previous findings for TRPC5 region‐specific protein expression . Together, our results clearly demonstrate a widespread distribution of TRPC5‐specific binding sites in the rat brain.…”
Section: Resultssupporting
confidence: 93%
“…In TRPC5 KO mice, seizure and neuronal cell death induced by pilocarpine was significantly reduced [ 34 ]. In cortical lesions of the focal cortical dysplasia, common intractable epilepsy in both pediatric and adult patients, the expression of TRPC5 is significantly increased in glutamatergic and GABAergic neurons [ 46 ]. Consistently, in our results, TRPC5 mRNA and protein were predominantly expressed in neurons than astrocytes, cell death was dependent to the expression of TRPC5, and NU6027, an inhibitor of TRPC5, reduced neuronal death in cortical cultures.…”
Section: Discussionmentioning
confidence: 99%
“…TRPV channels (e.g., vanilloid receptors and capsaicin receptors) have been shown to play a role in long-term depression in the hippocampus (47) and in glutamate release in the solitary tract nucleus (48). Tissue specimens from patients with type IIb FCDs and TSC show increased expression of TRPV channels, whereas control specimens show little TRPV (49). Electrophysiological studies have demonstrated that activation of these channels produces an increase in Ca 2+ in the cell, but the exact role these channels play in epilepsy and epileptogenesis remains unknown (50).…”
Section: Expression Of Other Cell Surface Receptors and Neuropeptidesmentioning
confidence: 99%